The Analysis of Fuzzy Qualitative Comparison Method and Multiple Case Study of Entrepreneurial Environment and Entrepreneur Psychology for Startups—Evidence From Guangdong-Hong Kong-Macao Greater Bay Area and Southeast Asia - Chu, Chien-Chi; Zhou, Zhi-Hang; Wang, Xin; Wu, Haichao; Tian, Yue; Cai, Zepai (Frontiers in Psychology, 2022)
Recently, scholars have begun to shift focus toward the idea to markelization of startups and the relationship with entrepreneurial psychology or other factors, However, the establishment of a unified and clear standard of entrepreneurship educational methods remains unfulfilled.We study investigates 28 representative Startups in four industries, includinng financial technology, biotechnology, education, and cultural tourism areas in Guangdong-Hong Kong-Macao Greater Bay Area (GBA) and Southeast Asia to obeserve different background but some factors matters in common for building entrepreneurship education systems and  methods in different countries. We used the fuzzy qualitative comparison method (fsQCA) to survey Startups entrepreneurs and executives through questionnaires, selecting Starups key factors including entrepreneurial psychology (optimism, passion, self-efficacy), product advantage, market and cultural environment, entrepreneurial policy, and geographical advantage. The survey was conducted on six key variables, namely, geographical advantage, to observe the conditional grouping and paths of factors influencing the establishment of Startups from an overall perspective. This study explores the path combination that plays a key role in the establishment of new enterprises, and further uses specific industry cases to verify the rationality and credibility of the path combination. The main conclusions are as follows:(1) There are five combination paths affecting the establishment of new enterprises, which are "psychology and product", "psychology, culture and policy", "psychology and region", "psychology and market" and "market and policy" combination paths;(2) Entrepreneur psychology, market environment and entrepreneurship policy are the core conditions to improve the effect of the establishment of new enterprises, while the other three variables are non-core variables in different paths;(3) There are different paths of entrepreneurial paths and factor combinations in different regions or industries.